Auger cascade initiated by the Coster–Kronig transition from the Kr 3p core-hole states. (20th October 2021) - Hikosaka, Y; Lablanquie, P; Kaneyasu, T; Adachi, J; Tanaka, H; Suzuki, I H; Ishikawa, M; Odagiri, T
Abstract: The full Auger cascade initiated by the M2, 3 M4, 5 N Coster–Kronig (CK) transitions from the Kr 3p core-hole states is revealed by using a multi-electron coincidence method. The individual CK transitions are located on the basis of the energy correlations between the Auger electrons emitted in the CK and secondary Auger transitions. The decay processes of the CK-final Kr 2+ states are investigated, whereby two-electron emissions leading to the formation of Kr 4+ levels are identified.